The Mediating Role of Environmental Sustainable Development Between Corporate Social Responsibility and Green Innovation - Sabihaini Sabihaini; Januar Eko Prasetio; Suyatno Ladiqi; Hamizah Binti Abdul Rahman; Rusdiyanto Rusdiyanto (International Journal of Accounting and Finance in Asia Pasific (IJAFAP), 2026)
Amid the escalating global climate crisis, recycling firms are increasingly expected to integrate social responsibility with environmentally sustainable practices and green innovation. This study examines the mediating role of environmental sustainable development (ESD) in the relationship between corporate social responsibility (CSR) and green innovation (GI) in Indonesia’s recycling industry. Using a quantitative survey, data were collected from 129 recycling companies and analyzed through SEM-PLS. The results show that CSR positively affects ESD (? = 0.684; p 0.001) and GI (? = 0.343; p 0.001), while ESD also positively affects GI (? = 0.401; p 0.001). The indirect effect of CSR on GI through ESD is significant (? = 0.271; p 0.001), indicating partial mediation because the direct CSR–GI path remains significant. These findings suggest that CSR contributes to green innovation more effectively when translated into resource-saving, waste-reducing, and environmentally sustainable development practices. The study extends CSR and green innovation literature and offers practical guidance for recycling firms seeking to align sustainability commitments with competitive, low-carbon innovation strategies.